Manila: Aspiring To Be an Inclusive, Resilient, and Sustainable City Amidst Climate and Disaster Risks - Porio, Emma E (Archīum Ateneo, 2023)
Metro Manila is one of the most rapidly urbanising metropolitan areas in Asia. Rapid urbanisation, intensified capitalist development, and consumption-driven lifestyles drive the social-ecological transitions of the city, exacerbating the climate and disaster impacts on its vulnerable communities. This chapter highlights how Manila's geographical and environmental contexts interact in complex ways with its socio-economic characteristics, resulting in a settlement pattern that poses high risks to its residents. In response, multi-sectoral initiatives are being pursued to co-produce science-based, risk-informed, and socially inclusive tools for building community resilience. The chapter provides an illustrative initiative: The Coastal Cities at Risk in the Philippines (CCARPH). CCARPH is a transdisciplinary action research consortium of multiple stakeholders, working together to produce climate and disaster risk assessment for planning and climate action by local government units (LGUs). The chapter argues that CCARPH's initiatives have resulted in the adoption of resilience-informed frameworks and tools across a number of local governments in Manila. CCARPH has also integrated the Social Development Goals (SDGs) into the resilience agenda of LGUs and allied partners. Moving forward, the Philippine government has mainstreamed the SDGs into various development plans in the country, pushing forward its aspiration to become resilient and sustainable into the future.